2015
DOI: 10.3390/molecules201219751
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Replacing Fish Meal in the Diet with Enzyme-Treated Soybean Meal (HP310) on Growth and Body Composition of Rainbow Trout Fry

Abstract: Abstract:The potential of enzyme-treated soybean meal powder (HP310) as fish meal alternative in diets for rainbow trout weighing 1.17˘0.3 g was evaluated for 60 days. Fish meal was replaced with HP310 at 25%, 50%, 75% and 100% of experimental diets. A control group was also considered. The results showed that diets containing 75% and 100% HP310 had significantly higher feed conversion ratio and lower feed intake, weight gain and specific growth rate compared to fish feed diets containing higher levels of fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…Proper diet formulation is one of the most important factors in commercial aquaculture as feed production costs and associated impact on subsequent fish growth are major expenses (Haghbayan & Shamsaie Mehrgan, ). Fish meal (FM) is the primary source of protein in fish feed (Gatlin et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proper diet formulation is one of the most important factors in commercial aquaculture as feed production costs and associated impact on subsequent fish growth are major expenses (Haghbayan & Shamsaie Mehrgan, ). Fish meal (FM) is the primary source of protein in fish feed (Gatlin et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Fish meal (FM) is the primary source of protein in fish feed (Gatlin et al., ). It is produced by processing whole, or parts of, fish and is known to be a highly nutritious and palatable protein source (Ding, Zhang, Ye, Du, & Kong, ; Haghbayan & Shamsaie Mehrgan, ). However, the continued growth of the aquaculture industry has been limited by a shortage in global production of, and competition for, FM by livestock and poultry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved growth performance by phytase in fish diet have also be reported for juvenile Clarias gariepinus fed diet based on full fat soya bean [18]. Haghbayan and Mehrgan, [59] reported growth improvement in rainbow trout fed soya bean diet supplemented with enzyme complex. Although a possibly higher than 0.40% available phosphorus by phytase was reported [17], the highest growth achieved at 250 FTU/g, with a corresponding available phosphorus of 0.53% compared to 0.54% recorded for 1000 FTU/g, which recorded the lowest growth performance compared to control, 250, 500 and 750 FTU/g phytase, showed that the available phosphorus of 250 FTU/g (0.53%) and phosphorus of 0.81% may be required for optimum growth performance of juvenile C. gariepinus.…”
Section: Discussionmentioning
confidence: 83%
“…In this research, the underlying mechanisms of action of herbal plants on the growth of fish are not well understood. Such reports indicated that active compounds found in the plant extracts may potentially improve feed intake, nutrient digestion, metabolism, and absorption capacity of the nutrients by increasing the activities of certain intestinal digestive enzymes (Haghbayan and Mehrgan, 2015;Mohammadi et al, 2018;Sewaka et al, 2019). Furthermore, scientific studies have demonstrated that positive effects of diets supplemented with phytogenic additives would directly induce the expression of growth hormone (GH) and insulin-like growth factors (IGFs) mRNA in order to promote muscle cell proliferation and differentiation, resulting in a pronounced increase in the growth rate of fish (Sruthi et al, 2018;Ahmadifar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%